NKIM-6, a new immortalized human brain capillary endothelial cell line with conserved endothelial characteristics - Ketabi-Kiyanvash, Nahal; Herold-Mende, Christel; Kashfi, Farzaneh; Caldeira, Sandra; Tommasino, Massimo; Haefeli, Walter E.; Weiß, Johanna (Cell & tissue research, 2007)
Primary human brain capillary endothelial cells (hBCECs) are available only in small quantities and have a short life span in vitro; this restricts their use as in vitro model for the blood-brain barrier (BBB). To overcome these limitations, we have established an immortalized hBCEC line (NKIM-6) by transfection with pLXSN16E6E7, which encodes the human papillomavirus type 16 E6 and E7 genes. The cell line exhibits an extended life span in vitro and retains its characteristic endothelial morphology, endothelial markers, and physiology. Likewise, as demonstrated by immunohistochemistry and reverse transcription/polymerase chain reaction (RT-PCR), NKIM-6 cells express BBB markers, and the lack of glial, neuronal, and epithelial markers confirms their endothelial origin. Moreover, with quantitative RT-PCR, we have been able to demonstrate that several ATP-binding cassette-transporters are expressed in NKIM-6 cells with a conserved expression order compared with primary hBCECs. Our results suggest that this cell line might be suitable as in vitro model for several aspects of the BBB.
Published: 19 December 2006
Gesehen am 12.05.2021